Epigenetic Matters: The Link between Early Nutrition, Microbiome, and Long-term Health Development - Indrio, Flavia; Martini, Silvia; Francavilla, Ruggiero; Corvaglia, Luigi; Cristofori, Fernanda; Mastrolia, Salvatore Andrea; Neu, Josef; Rautava, Samuli; Russo Spena, Giovanna; Raimondi, Francesco; Loverro, Giuseppe (Frontiers in Pediatrics, 2017)
Epigenetic modifications are among the most important mechanisms by which environmental factors can influence early cellular differentiation and create new phenotypic traits during pregnancy and within the neonatal period without altering the DNA sequence. A number of antenatal and postnatal factors, such as maternal and neonatal nutrition, pollutant exposure and the composition of microbiota, contribute to the establishment of epigenetic changes that can not only modulate the individual adaptation to the environment, but also have an influence on lifelong health and disease by modifying inflammatory molecular pathways and the immune response. Post-natal intestinal colonization, in turn determined by maternal flora, mode of delivery, early skin-to-skin contact and neonatal diet, leads to specific epigenetic signatures that can affect the barrier properties of gut mucosa and their protective role against later insults, thus potentially predisposing to the development of late-onset inflammatory diseases. The aim of this review is to outline the epigenetic mechanisms of programming and development acting within early life stages, and to examine in detail the role of maternal and neonatal nutrition, microbiota composition and other environmental factors in determining epigenetic changes and their short- and long-term effects.